Två furstendömen - En komparativ fallstudie om storlek och demokrati i Liechtenstein och Monaco - Tidén,Noah (2023)
It is in political scientific theory commonly understood that the politics of microstates are defined by a lack of ideological plurality and strong public consensuses. This study aims to investigate whether such characteristics may contribute to the emergence of party systems that hinder the full democratization of countries. The study has been conducted as a multiple-case study including the principalities of Liechtenstein and Monaco. Although case studies are limited in scope and do not provide sufficient data to draw definite generalizable conclusions, the results of this study indicate a probable link between country size and political structure. Both Liechtenstein and Monaco are politically dominated by conservative, center-right parties and have been so for as long as they have been democratic. Two possible explanations for this that have been suggested in this paper are: (1) neither of the two countries have ever had the prerequisite conditions for the emergence of political cleavages that produce differentiated party systems, and (2) the public debate is constrained by a culture of consensus wherein individuals professing unorthodox political views, e.g. on the role of the ruling princely house, are regarded as eccentrics and discounted from the realm of reasonable public discourse.
Keywords: Size and democracy; party system; microstates; Liechtenstein; Monaco; cleavages; consensus